Comparative transcriptome analysis of the molecular mechanism underlying the golden red colour in mutant Taiwanese loach - Huang, Zhihui; Ma, Benhe; Guo, Xiaoli; Wang, Haihua; Ma, Aijun; Sun, Zhibin; Wang, Qingmin (Aquaculture, 2021)
Taiwanese loach (Paramisgurnus dabryanus ssp. Taiwan) have mutant phenotypes with golden-pink eyes and golden-red body colour without any blotches. We consider this colour variation comparable to albinism reported in other species. However, the molecular mechanism underlying these mutations is unknown. In the present study, we conducted a comparative analysis of transcripts from the skin of wild-type and mutant fish. A total of 6516 differentially expressed genes (DEGs) were identified, including 3317 (50.9%) upregulated unigenes and 3199 (49.1%) downregulated unigenes in mutant individuals. Additional annotation comparing known pigmentation genes and KEGG pathway analysis indicated that the melanogenesis pathway is the key pathway regulating pigment synthesis. Oca2, slc45a2 and mc1r were identified as potential genes associated with albinism. Analysis of the top 10 KEGG pathways revealed that some DEGs were liked to lipid metabolism, such fish skin transcriptome results have not been reported previously. The fatty acid composition of fish skin was analysed by gas chromatography, and the results were consistent with the RNA-Seq analysis. We propose that cells possess intrinsic mechanisms to dampen inflammation and avoid excessive damage, resulting in albino mutants. This is the first report of a mutant-type (golden-red albinism) Taiwanese loach with golden-red skin colour from fish farms in China. The findings provide a basis for studying the molecular mechanism underlying the abnormalities of pigmentation, and will facilitate the future genetic selection and breeding of Taiwanese loach in aquaculture. •This is the first study on the transcriptomic of the mutant Taiwanese loach with golden-red skin.•Melanogenesis pathway is the key pathway, and alteration of key genes may lead to albinism.•This is the first report of lipid metabolism were significantly elevated in the skin of MR fish.•It provides new insights into the molecular mechanism of golden-red mutant loach.